Prevalence of cancer-related fatigue, associated factors and adult cancer patients’ experiences at Hawassa University Comprehensive Specialized Hospital in Ethiopia: a mixed methods study - Asefa, Tseganesh; Bitew, Gedamnesh; Tezera, Hiwot; Tesfaye, Winta (Frontiers in Oncology, 2024)
PurposeCancer-related fatigue is a prevalent issue affecting 50–90% of cancer patients who experience fatigue at diagnosis, during therapy, and often for months or years after the completion of therapy. This study aimed to explore the prevalence of cancer-related fatigue, associated factors, and adult cancer patients’ experiences at Hawassa University Comprehensive Specialized Hospital in Ethiopia.MethodsA mixed-method study was conducted from February 25 to May 15, 2023, via cross-sectional descriptive and phenomenological approaches. The validated Amharic Brief Fatigue Inventory scale and semistructured interview guide were used. The data were processed via Epi-data version 4.4.3.1 and SPSS version 24, with logistic regression analysis. The interview records and field notes were transcribed and translated from Amharic to English and then analysed thematically.ResultsAll participants (100%) completed the study, with 77.4% reporting significant fatigue. Fatigue was strongly associated with uninsured medical expenses (P = 0.008, OR = 3.22), late-stage cancer (P = 0.000, OR = 6.11), anaemia (P = 0.009, OR = 3.71), and comorbidities (P = 0.000, OR = 7.22). From the in-depth interviews with 16 participants, two main themes emerged: financial strain (giving up basics, and inability to work) and disease progression (intensified symptoms, increased treatment side effects, and managing multiple conditions).ConclusionThis study revealed that 77.4% of cancer patients experience significant fatigue, which is linked to a lack of medical insurance, late-stage cancer, anaemia, and comorbid conditions. Financial strain limits access to care, whereas disease progression and managing multiple conditions intensify fatigue. Early intervention, financial support, and integrated care are crucial for reducing fatigue and improving quality of life. Future research should focus on multicentre and longitudinal studies to improve generalizability and track fatigue progression over time.